TEACHER’S STRATEGY IN DEALING WITH STUDENTS’ MISBEHAVIOR IN SMPN 1 LASALEPA SUBDISTRICT OF MUNA REGENCY - Rahmawati, Yuli; Sale, Firdaus; Suhartini, Lelly (Journal of Teaching of English, 2019)
This study aimed at knowing the types of students’ misbehavior mostly happened in the learning process and strategy  that  teacher used  in dealing  with the  students’ misbehavior  at  the  first  and second grade in SMPN 1 Lasalepa. The researcher employed descriptive as the design of the study where observation was used to collect the data. The results of the study showed that the misbehavior  of  students  mostly  happened  in  the  class were:  talking  during  the  class,  lack  of  concentration, joking, laziness, daydreaming, disobedience and running about the class. Then, teachers’ strategies used in dealing with the students’ misbehavior were: asking the students calmly but strictly to stop the students’ behavior problems, ignoring the students’ misbehavior and not paying attention to it, walking toward the student and getting physically close to them, and giving students questions in the classroom. As the result, it is necessary to be known due to  problems always come in the class and teachers need  to  know  the  kinds  of  the  problem  and  need  to prepare the appropriate strategies to handle the problems properly in order to not disturb the learning process. Keywords: Students’ Misbehavior, Teachers’ Strategies, Learning Process